Correction to: A loop-mediated isothermal amplification assay for the detection and quantification of JC polyomavirus in cerebrospinal fluid: a diagnostic and clinical management tool and technique for progressive multifocal leukoencephalopathy - Hitomi Kinoshita (Virology Journal, 2018)
In the original publication of article [1], ‘20 × 101 copies’, which is in the sentence ‘As seen in Fig. 4, the sensitivity of the specimens containing equal to or more than 20 × 10 1 copies in 2 μL of extracted DNA (equivalent to ≥3.0 × 103 copies/mL CSF) was 100% (29/29)’ changes to ‘2.0 × 101 copies’ in results section. The publisher apologizes to the readers and authors for the inconvenience.